Faculty Senate, Minutes, February 17, 2011 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2011)
Valdosta State University. Faculty Senate, Minutes, February 17, 2011. Chairperson, Patrick J. Schloss; Vice Chairperson, Philip Gunter; Executive Secretary, Peggy L. Moch; Parliamentarian, Ed Walker;
1 electronic document. Faculty Senate, Minutes, February 17, 2011. 30 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records